Benefit and risk of intravenous alteplase in patients with acute large vessel occlusion stroke and low ASPECTS. (25th January 2022) - Broocks, Gabriel; McDonough, Rosalie; Bechstein, Matthias; Hanning, Uta; Brekenfeld, Caspar; Flottmann, Fabian; Kniep, Helge; Nawka, Marie Teresa; Deb-Chatterji, Milani; Thomalla, Götz; Sporns, Peter; Yeo, Leonard LL; et al.
Abstract : Background: The benefit of best medical treatment including intravenous alteplase (IVT) before mechanical thrombectomy (MT) in patients with acute ischemic stroke and extensive early ischemic changes on baseline CT remains uncertain. The purpose of this study was to evaluate the benefit of IVT for patients with low ASPECTS (Alberta Stroke Programme Early CT Score) compared with patients with or without MT. Methods: This multicenter study pooled consecutive patients with anterior circulation acute stroke and ASPECTS≤5 to analyze the impact of IVT on functional outcome, and to compare bridging IVT with direct MT. Functional endpoints were the rates of good (modified Rankin Scale (mRS) score ≤2) and very poor (mRS ≥5) outcome at day 90. Safety endpoint was the occurrence of symptomatic intracranial hemorrhage (sICH). Results: 429 patients were included. 290 (68%) received IVT and 168 (39%) underwent MT. The rate of good functional outcome was 14.4% (95% CI 7.1% to 21.8%) for patients who received bridging IVT and 24.4% (95% CI 16.5% to 32.2%) for those who underwent direct MT. The rate of sICH was significantly higher in patients with bridging IVT compared with direct MT (17.8% vs 6.4%, p=0.004). In multivariable logistic regression analysis, IVT was significantly associated with very poor outcome (OR 2.22, 95% CI 1.05 to 4.73, p=0.04) and sICH (OR 3.44, 95% CI 1.18 to 10.07, p=0.02). Successful recanalization, age, and ASPECTS were associated with good functional outcome. Conclusions: Bridging IVT in patients with low ASPECTS was associated with very poor functional outcome and an increased risk of sICH. The benefit of this treatment should therefore be carefully weighed in such scenarios. Further randomized controlled trials are required to validate our findings.